2006
DOI: 10.2165/00002018-200629030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rabbit Purkinje Fibre Assay as an in vitro Tool for Assessing the Risk of Drug-Induced Torsades de Pointes in Humans

Abstract: The rabbit Purkinje fibre is a valuable assay for evaluating the proarrhythmic liability of pharmaceuticals as it can reveal complex electrophysiological profiles that modulate repolarisation delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 35 publications
0
20
2
Order By: Relevance
“…Both the Food and Drug Administration and the European Medicines Agency recommend the Purkinje fiber assay for in vitro electrophysiological studies as valuable for assessing potential arrhythmogenicity of a tested compound (41). Aubert et al (2) have specifically evaluated the rabbit Purkinje fiber assay on 26 potentially arrhythmogenic compounds. They found that the number of false positives and false negatives was better than any similar assay from other animal species.…”
mentioning
confidence: 99%
“…Both the Food and Drug Administration and the European Medicines Agency recommend the Purkinje fiber assay for in vitro electrophysiological studies as valuable for assessing potential arrhythmogenicity of a tested compound (41). Aubert et al (2) have specifically evaluated the rabbit Purkinje fiber assay on 26 potentially arrhythmogenic compounds. They found that the number of false positives and false negatives was better than any similar assay from other animal species.…”
mentioning
confidence: 99%
“…Thus, it appears that it is a highly specific and sensitive model to investigate drug-induced TdP liability. Over the years, the assay has been well validated through the testing of many reference compounds (see Champeroux et al 2005;Hanson et al 2006;Aubert et al 2006;Puddu et al 2011) for use in the early de-risking stages of development (as a non-GLP assay) or as a component of the GLP-compliant in vitro core battery testing scheme. Over the years, the assay has been well validated through the testing of many reference compounds (see Champeroux et al 2005;Hanson et al 2006;Aubert et al 2006;Puddu et al 2011) for use in the early de-risking stages of development (as a non-GLP assay) or as a component of the GLP-compliant in vitro core battery testing scheme.…”
Section: The Isolated Purkinje Fibrementioning
confidence: 99%
“…Variations on the AP shape are indicative of the potential effects of the substance on the main cardiac ionic currents such as the rapid sodium current (I Na ) responsible for the rapid cell depolarization (phase 0 of the AP) and involved in cell electrical conductance, the transient outward potassium current (I Kto ) responsible for the notch specific to the Purkinje fiber AP (phase 1 of the AP), the slow calcium current (I CaL ) partly responsible for the maintaining of the AP plateau (phase 2 of the AP) and involved in the contractile properties of the cardiomyocytes, the slow and rapid components of the delayed rectifier potassium current (I Ks and I Kr ) mainly responsible for the cell late repolarization (phase 3 of the AP), and the inward rectifier potassium current (I K1 ) that helps in the maintenance of the cardiac cell hyperpolarization at rest (phase 4 of the AP). Most of Purkinje fiber studies are conducted in rabbit or dog preparations either because of the high sensitivity of the rabbit cardiac preparation to AP duration variations [22,23] or because comparison of ex vivo and in vivo data (QT interval on dog ECG) are facilitated by use of the same animal species [24,25]. Some scientists claim that the rabbit Purkinje fiber is too much sensitive to AP duration lengthening to be accurately predictive for human and that it would present a high risk of false positive, particularly when Purkinje fibers are removed from females that have been shown as more sensitive than males to such effects [26].…”
Section: Ex Vivo Multicellular Studies On Surrogate Biomarkers Of Promentioning
confidence: 99%